IMPLEMENTATION OF PROJECT BASED LEARNING TO IMPROVE THE ABILITY TO COOPERATE WITH CHILDREN AGED 5-6 YEARS AT SRITANJUNG BANGUNSARI INDERGARTEN BANYUWANGI ACADEMIC YEAR 2023/2024 - Darmasanti Nakluh Yekti; Zahro Ianatuz; Suwargono Trio (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
The aim of this research is to determine the application of project based learning to improve the collaboration abilities of children aged 5-6 years at Sritanjung Bangunsari Banyuwangi Kindergarten for the 2023/2024 academic year. The object of this research is group B with a total of 11 children consisting of 6 boys and 5 girls. The type of research used in this research is classroom action research (PTK). In this research, there are two instruments used to collect data, namely observation and documentation. The indicators in this research are: 1) Children are able to stick to pictures in their group, 2) Children are able to tell about their own work that has been made in their group, 3) Children are able to differentiate between plant-eating animals, meat-eating animals, giving birth animals and egg-laying animals. The results of observations on the pre-cycle of children's cooperative abilities were 9 out of 11 children or 81.8% of the children's cooperative abilities (BB), 2 out of 11 children or 18.1% of the children were beginning to develop (MB), the criteria were developing according to expectations ( BSH) and very well developed (BSB) have not been found or 0%. In the Pre-Cycle the child's language proficiency level reached 24.5%. In Cycle I, children's ability to cooperate under the criteria of not yet developing (BB) was 2 out of 11 children or 18.1%, under the criteria starting to develop (MB) there were 6 out of 11 children or 54.5%. There were 3 children out of 11 who got a score of developing according to expectations (BSH) or 27.2%. The criteria for very well developed (BSB) have not been found or 0%. In the first cycle, the level of children's language skills increased to 50.3%. In Cycle II, children's ability to work together on the criteria of developing very well (BSB) reached the highest score, namely 72.7% or 8 out of 11 children, on the criteria of developing according to expectations (BSH) there were 3 children out of 11 children with a percentage of 27.2%. The criteria for starting to develop (MB) and not yet developing (BB) are no longer there or 0%. Thus, it can be concluded that the application of Project-Based Learning can improve children's cooperation abilities because there are 8 children who have achieved the specified indicators, namely the criteria for very good development (BSB) with a percentage of 72.7% of the total number of children. In cycle II, the level of children's cooperation abilities had reached the success indicator with an average value of 93.9%.